Share your smile : Raina's guide to telling your own story - Telgemeier, Raina (New York, N.Y. : Graphix, an imprint of Scholastic, 2019)
Have you ever thought about telling your own story, whether it be true or imagined? Are you interested in writing, drawing, or both? If the answers are yes, this fun, colorful, and interactive journal is for you! With guidance from Raina herself, brainstorm ideas, make lists, paste in personal photos, and use your imagination like never before to create your own stories. For additional inspiration, behind-the-scenes info from Raina's own comics-making adventures is featured inside.
Offers writing prompts, activities, and tips and techniques for writing and illustrating a story.
Keywords: Authorship -- Comic books, strips, etc; Authorship -- Vocational guidance -- Comic books, strips, etc